Viability of freshly prepared cells derived from foetal brain of rabbit at different temperature settings during transportation - Abdul Razak, Redzuan Nul Hakim; Mazlan, Muhammad Alif; Ahmad, Azmir; Abd. Jalil, Mohd. Azri; Abdul Jalil, Abdul Halim; Md Isa, Muhammad Lokman (Malaysian Society for Biochemistry and Molecular Biology, 2020)
The characteristics of rabbit cells, i.e., high proliferative activity, high passage numbers, and morphologically similar to human cells renders it a potential source of a cell line. Nonetheless, they are not widely characterised for research purposes. This study aimed to observe the effects of different temperature settings on the viability of rabbit foetal brain (RFB) cells at different time points. The harvested RFB cells were divided into room temperature (RT), ice packs (ICE), and refrigerator (4 °C) groups. Cell viability was determined at 0, 6, 12, 24, 48, and 72 h. Following cell viability determination, the cells were recultured for 24 h to observe cell viability and morphology post-transportation. The cell viability was analysed statistically for within and more than 24 h duration using the one-way ANOVA test, and the cell morphology was observed under the microscope. For the within 24 h analysis, the ICE group showed the best condition for 24 h transportation due to significantly higher cell viability (p<0.05) compared to the RT group. Meanwhile, for the more than 24 h analysis, the RT group showed the best condition for more than 24 h transportation due to higher cell viability compared to the ICE and 4 °C groups, albeit the non-significance. The reculturing of RFB cells showed no remarkable difference in the cell viability and morphology in all transportation time points at all temperature settings. In conclusion, the study found that the RFB cells are suitable to be transported using ice packs for transportation within 24 h and room temperature for transportation of more than 24 h.